CHILDREN OF THE MOTHERLAND (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The role of Fayzulla Khojayev and Usmon Yusupov in the history of our country is of special importance. Because these two individuals have served their political careers for their homeland. These articles about their political activities are discussed in detail. Our article about the real children of Uzbekistan.